Tunnel lining efficient water plugging and reinforcing rapid-hardening mineral-based cementing material
By using fast-condensing mineral-based gelling materials and graphene oxide external admixtures in tunnel lining water blocking materials, the problems of high water secretion and slow gelling speed of traditional water blocking materials are solved, and the effects of efficient water blocking, rapid curing and strength improvement are achieved.
Patent Information
- Application Number
- CN202411761773.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-04-15
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Traditional tunnel lining water blocking materials have performance defects such as large water secretion, slow gelation speed, and large curing and shrinking, which is difficult to effectively solve the problem of tunnel water stop.
A tunnel lining is used to strengthen fast-condensing mineral-based gelling material. This material uses alkaline excitation activity and the crystallization principle of natural mineral formation and the chemical process principle of natural colloid formation, and adds external dopants such as graphene oxide and potassium hydroxide to improve the flow of cement slurry, reduce the water secretion rate, increase the stone rate, and enhance the later strength.
This material has water-free, fast gelling, rapid curing, strong dilution resistance, strong permeability, good infusion ability, good early strength, fast strength, strong final strength, strong permeability, strong vibration resistance, and good water stability. It can effectively block the tunnel surrounding rock seepage channels and improve the strength of soil or crack surrounding rocks.
Smart Images

Figure BDA0005167881280000061 
Figure BDA0005167881280000062 
Figure BDA0005167881280000071
Abstract
Description
Technical Field
[0001] The invention relates to a tunnel lining water blocking and reinforcement material, in particular to a tunnel lining high-efficiency water blocking and reinforcement fast-setting mineral-based cementitious material. Background Art
[0002] Leakage in traffic tunnels will inevitably lead to water accumulation between the lining and the surrounding rock, long-term dissolution of the lining concrete, damage to the lining structure and strength degradation, and other problems and safety hazards. The "water stopping" problem must be solved first. Traditional methods mostly use traditional grouting technology with low cost, simple technology and fast construction. Cement-based grouting materials are poured into the tunnel lining or surrounding rock to block the surrounding rock seepage and lining cracks. Cement slurry materials are also used to reinforce crack linings or to combine densely distributed anchor rods and I-beams to reinforce linings. However, due to the important performance defects of cement grouting materials such as large water permeability, slow gelation speed, and large curing shrinkage, the grouting effect is very limited and difficult to be effective in the long term. In addition, the groundwater seepage in the surrounding rock is not considered. Moreover, the current grouting technology is difficult to meet the requirements of rapid construction using a short "skylight" time. Therefore, these methods "treat the symptoms but not the root cause" and fail to fundamentally solve the "water" problem. Therefore, it is necessary to develop a fast-setting mineral-based cementitious material suitable for tunnel lining water blocking and reinforcement to fundamentally solve the technical problems of tunnel water stopping. Summary of the invention
[0003] In view of the problems existing in the tunnel lining water blocking materials and production processes at the current stage, the present invention provides a fast-setting mineral-based cementitious material for high-efficiency water blocking and consolidation of tunnel lining. The fast-setting mineral-based cementitious material uses alkaline activating activity and the crystallization principle of natural mineral formation and the chemical process principle of natural colloid formation, and uses alkaline activators such as graphene oxide and potassium hydroxide as admixtures, which can improve the fluidity of cement slurry, reduce water seepage rate, increase stone rate, enhance later strength, improve the internal structure of lining water blocking materials, and improve anti-seepage ability.
[0004] The objective of the present invention is achieved through the following technical solutions:
[0005] A high-efficiency water-blocking and fast-setting mineral-based cementitious material for tunnel lining, comprising the following raw materials in parts by weight: 20-40 parts of sulphoaluminate cement, 20-40 parts of silicate cement, 5-10 parts of fly ash, 2-6 parts of wollastonite powder, 1-5 parts of quicklime, 0-5 parts of retarder, 1-3 parts of aluminum oxide, 0.5-1.5 parts of potassium hydroxide, 1-2 parts of magnesium oxide, 0.5-1.5 parts of calcium sulfate, 2-3 parts of graphene oxide nanosheets, and 0.2-0.5 parts of water reducer. Among them: the wollastonite powder is 800-1250 mesh, and the Si content is more than 60%; the calcium oxide content in the quicklime is more than 80%; the average thickness of the graphene oxide nanosheets is about 1nm; the water reducer is a polycarboxylic acid high-performance water reducer or a naphthalene-based high-efficiency water reducer, the Na2SO4 content in the naphthalene-based high-efficiency water reducer is less than 3%, and the water reduction rate of the polycarboxylic acid high-performance water reducer is 15-25%; the fly ash is secondary fly ash or primary fly ash; the retarder is citric acid.
[0006] A method for using the above-mentioned tunnel lining high-efficiency water blocking and reinforcement rapid-setting mineral-based cementitious material comprises the following steps:
[0007] Step 1: Evenly mix sulphoaluminate cement, silicate cement, fly ash, wollastonite powder, quicklime, retarder, alumina, potassium hydroxide, magnesium oxide, calcium sulfate, graphene oxide nanosheets and water reducer according to the above weight parts;
[0008] Step 2: Add pure water and stir evenly until the viscosity of the funnel is within 30s, then it is ready to be formed.
[0009] In the present invention, the functions of each raw material are as follows:
[0010] (1) Cement hydrolysis, hydration reaction, ion exchange, and carbonation
[0011] When cement meets water, it will undergo hydrolysis and hydration reaction during the hardening process to produce hydrated calcium silicate gel, calcium hydroxide, hydrated calcium aluminate, hydrated calcium ferrate, hydrated calcium sulfoaluminate and other crystals. Cement hydration produces Ca(OH)2 ionized Ca 2+ With K in admixture + and Na + Equal ion exchange occurs, making the double-electrode membrane thinner and the cement hardened body more compact. At the same time, the Ca(OH)2 generated by the hydration reaction reacts with CO2 in the air or HCO3 in the water. - The production of CaCO3 increases the strength of the material.
[0012] (2) Hydration reaction of magnesium oxide and quicklime
[0013] When magnesium oxide and quicklime meet water, they generate magnesium hydroxide and calcium hydroxide, which expand the volume of the hardened cement slurry, enrich the interface transition zone, and also provide an alkaline environment, accelerating the hydrolysis and hydration reaction of the cement.
[0014] (3) Reaction of wollastonite powder, alumina, calcium sulfate and cement
[0015] The CaO·SiO2 (C3A) in cement reacts with CaSO4 in water to form ettringite (C3A·3CaSO4·32H2O), which further hydrates to produce calcium hydroxide (Ca(OH)2) and calcium carbonate (CaCO3):
[0016] C3A+CaSO4+H2O→C3A·3CaSO4·32H2O (1)
[0017] CaO+H2O→Ca(OH)2 (2)
[0018] CaO+CO2→CaCO3 (3)
[0019] Wollastonite powder (SiO2) and alumina (Al2O3) will further react with calcium hydroxide Ca(OH)2, the hydration product of cement, to form hydrated calcium zeolite (CaAl2Si2O84H2O):
[0020] Ca(OH)2+Al2O3+SiO2+H2O→CaAl2Si2O84H2O (4)
[0021] The hydration reaction of cement during the curing period and the Ca(OH)2 produced by quicklime in water reach a critical state, while the silicon and aluminum in alumina and wollastonite powder still precipitate in large quantities in the form of acidic ions, decomposing the CaAl2Si2O84H2O generated in the early stage of the hydration reaction and neutralizing the alkaline environment inside the cement slurry. At this time, the divalent calcium ions react with the precipitated tetravalent silicon ions and trivalent aluminum ions to form calcium silicate hydrate (CSH), and the trivalent iron ions in the fly ash react with CSH in the interface transition zone to form calcium iron garnet (Ca(Fe 0.87 Al 0.13 )2(SiO4) 1.65 (OH)), improving the anti-seepage ability.
[0022] CaAl2Si2O84H2O+Fe 3+ →Ca(Fe 0.87 Al 0.13 )2(SiO4) 1.65 (OH) (5)
[0023] (4) Function of retarder: It regulates the initial setting time, facilitates grouting construction, and has no effect on strength.
[0024] (5) Function of water reducer: reduce the amount of water used and reduce the shrinkage rate of cement slurry hardening.
[0025] (6) Function of fly ash: Reduce water seepage rate.
[0026] 1) Fly ash particles are smaller than cement particles and have a much larger specific surface area than cement, so the adsorption of moisture is enhanced, thereby reducing the amount of free water secreted.
[0027] 2) The fine-particle fly ash increases the solid phase packing density in the concrete, refines the pores in the concrete, reduces the water seepage channels, increases the channel distance, and thus hinders the water secretion.
[0028] 3) Fly ash has a smaller density than cement particles. It is less likely for slurry sedimentation and segregation to occur. The uniformity of the mixture is better over time, which is beneficial to reduce water seepage.
[0029] (7) The role of graphene oxide:
[0030] 1) Filling effect: With the incorporation of graphene oxide, the pores of the cement hardener will be filled with nano-scale graphene oxide, thereby improving the pore structure of the material, making the microstructure denser and improving the anti-permeability.
[0031] 2) Bridging effect: With the incorporation of graphene oxide, cracks will be effectively refined and bridged, and cracks will twist around the graphene oxide sheets, giving the material a denser microstructure and improving its impermeability.
[0032] (8) Synergistic enhancement effect of graphene oxide and cement
[0033] 1) Nucleation effect: Graphene oxide has a large specific surface area and surface energy. During the hydration reaction, graphene oxide will adsorb cement and become the core of the hydration reaction, that is, the particles will be concentrated on the surface of graphene oxide particles. Therefore, the hydration reaction will be easier to proceed, forming a more dense hydrated calcium silicate gel, which provides greater possibilities for optimizing the microstructure and improving the impermeability.
[0034] 2) Promote cement hydration reaction: For cement grouting slurry, the improvement in strength is mainly due to the higher bonding force of calcium silicate gel, the hydration product of cement. Therefore, the more hydrogel is produced and the faster it is produced, the better the effect of enhancing strength. There are a large number of oxygen-containing functional groups (-OH, -COOH) on the surface of graphene oxide, which will promote the formation of hydrogel, thereby making the strength higher, the structure more compact, and the anti-seepage ability improved.
[0035] 3) Promote ion exchange: Ca generated by hydration 2+ K adsorbed to raw soil particles+ and Na + Equal ion exchange occurs, making the double electric membrane thinner and the cement hardening particles more closely connected. Due to the promotion of cement hydration by graphene oxide, more Ca 2+ , so that the ion exchange is more extensive and the exchange absorption is deeper, the reinforcement effect is better, and the strength of the grouting material is improved.
[0036] Compared with the prior art, the present invention has the following advantages:
[0037] (1) The tunnel lining water blocking reinforcement material of the present invention has many performance advantages such as no water seepage, rapid gelation, rapid solidification, slight expansion of gelation, strong dilution resistance, strong permeability and diffusion, good injectability, good early strength of stone body, rapid strength increase, high final strength, strong impermeability, strong vibration resistance, good water stability, etc. After solidification, this material expands slightly and becomes more dense, and has high bonding strength with soil particles, rocks, pore walls, and crack walls, so as to better block the seepage channel of tunnel surrounding rock (soil body) and improve the strength of soil or crack surrounding rock.
[0038] (2) Under standard curing conditions, the mass ratio of quick-setting mineral-based cementitious materials: water = 10:3, the 24-hour unconfined compressive strength can reach 30-35 MPa, and the 7-day unconfined compressive strength can reach 65-70 MPa. In a water-influent environment, the 24-hour unconfined compressive strength can reach 20-25 MPa, and the 7-day unconfined compressive strength can reach 50-55 MPa.
[0039] (3) The initial setting time of the slurry is controllable and easy to use.
[0040] (4) The quick-setting mineral-based cementitious material of the present invention is easy to use, reacts by adding water, has high strength and good durability, and can make the solidified body solidify normally under the influence of complex environments such as immersion environment, dry-wet cycle, freeze-thaw cycle and corrosive solution. DETAILED DESCRIPTION
[0041] The technical solution of the present invention is further described below in conjunction with the embodiments, but is not limited thereto. Any modification or equivalent replacement of the technical solution of the present invention without departing from the spirit and scope of the technical solution of the present invention should be included in the protection scope of the present invention.
[0042] Example 1
[0043] According to the material ratio in Table 1, a high-efficiency water-blocking and fast-setting mineral-based cementitious material for tunnel lining is prepared. The wollastonite powder is 800-1250 mesh, and the Si content is more than 60%; the calcium oxide content in the quicklime is more than 80%. The average thickness of the graphene oxide nanosheet is about 1nm. The content of Na2SO4 in the naphthalene-based high-efficiency water reducer is less than 3%. The fly ash is secondary powder.
[0044] The quick-setting mineral-based cementitious material is mixed uniformly according to the mass ratio of 10:3 to water to achieve a high degree of uniformity as much as possible; the quick-setting mineral-based cementitious material is carefully poured into a 100mm×100mm×100mm six-unit cubic steel test mold (mold), compacted by vibration, and 6 samples are prepared. A layer of plastic wrap is sealed on the upper part to prevent contact with the outside air and moisture loss. The samples are placed in a standard curing box (relative humidity 95%, temperature 20°C) and cured in a water environment for 24 hours. They are taken out after 7 days, and the unconfined compressive strength test is carried out. The average strength of the cured cement body is shown in Table 2.
[0045] Table 1 Proportion of fast-setting mineral-based cementitious materials for efficient water blocking and reinforcement of tunnel lining
[0046]
[0047] Table 2 Performance determination of fast-setting mineral-based cementitious materials for efficient water blocking and reinforcement of tunnel lining
[0048]
[0049] Example 2
[0050] According to the material ratio in Table 3, a high-efficiency water-blocking and fast-setting mineral-based cementitious material for tunnel lining is prepared. The wollastonite powder is 800-1250 mesh, and the Si content is more than 60%; the calcium oxide content in the quicklime is more than 80%. The average thickness of the graphene oxide nanosheet is about 1nm. The content of Na2SO4 in the naphthalene-based high-efficiency water reducer is less than 3%. The fly ash is first-class fly ash.
[0051] The quick-setting mineral-based cementitious material is mixed uniformly according to the mass ratio of 10:3 to water to achieve a high degree of uniformity as much as possible; the quick-setting mineral-based cementitious material is carefully poured into a 100mm×100mm×100mm six-unit cubic steel test mold (mold), compacted by vibration, and 6 samples are prepared. A layer of plastic wrap is sealed on the upper part to prevent contact with the outside air and water loss. The samples are placed in a standard curing box (relative humidity 95%, temperature 20°C) and cured in a water environment for 24 hours. They are taken out after 7 days, and the unconfined compressive strength test is carried out. The average strength of the cured cement body is shown in Table 4.
[0052] Table 3 Proportion of fast-setting mineral-based cementitious materials for efficient water blocking and reinforcement of tunnel lining
[0053]
[0054] Table 4 Performance determination of fast-setting mineral-based cementitious materials for efficient water blocking and reinforcement of tunnel lining
[0055]
[0056] Example 3
[0057] According to the material ratio in Table 5, a high-efficiency water-blocking and fast-setting mineral-based cementitious material for tunnel lining is prepared. The wollastonite powder is 800-1250 mesh, and the Si content is more than 60%; the calcium oxide content in the quicklime is more than 80%. The average thickness of the graphene oxide nanosheet is about 1nm. The content of Na2SO4 in the naphthalene-based high-efficiency water reducer is less than 3%. The fly ash is secondary powder.
[0058] Mix the quick-setting mineral-based cementitious material and water in a mass ratio of 10:3 until uniform, so as to achieve a high degree of uniformity as possible; carefully pour the quick-setting mineral-based cementitious material into a 100mm×100mm×100mm six-unit cubic steel test mold (mold), vibrate and compact it, prepare 6 samples, seal a layer of plastic wrap on the upper part to prevent contact with the outside air and moisture loss, put it into a standard curing box (relative humidity 95%, temperature 20°C) and cure it in a water environment for 24 hours, take it out after 7 days, and carry out unconfined compressive strength test. The average strength of the cured cement body is shown in Table 6.
[0059] Table 5 Proportion of fast-setting mineral-based cementitious materials for efficient water blocking and reinforcement of tunnel lining
[0060]
[0061]
[0062] Table 6 Performance determination of fast-setting mineral-based cementitious materials for efficient water blocking and reinforcement of tunnel lining
[0063]
[0064] Example 4
[0065] The difference between this embodiment and embodiment 1-3 is that a retarder citric acid is added to the rapid-setting mineral-based cementitious material, and the amount of the retarder added is 2 kg. The addition of the retarder has no effect on the strength.
Claims
1. A fast-setting mineral-based cementitious material for high-efficiency water blocking and reinforcement of tunnel lining, characterized in that The fast-setting mineral-based cementitious material includes the following raw materials in parts by weight: 20 to 40 parts of sulphoaluminate cement, 20 to 40 parts of silicate cement, 5 to 10 parts of fly ash, 2 to 6 parts of wollastonite powder, 1 to 5 parts of quicklime, 0 to 5 parts of retarder, 1 to 3 parts of aluminum oxide, 0.5 to 1.5 parts of potassium hydroxide, 1 to 2 parts of magnesium oxide, 0.5 to 1.5 parts of calcium sulfate, 2 to 3 parts of graphene oxide nanosheets, and 0.2 to 0.5 parts of water reducer.
2. The tunnel lining high-efficiency water blocking and reinforcement rapid-setting mineral-based cementitious material according to claim 1 is characterized in that The wollastonite powder has a mesh size of 800-1250 and a Si content of more than 60%.
3. The tunnel lining high-efficiency water blocking and reinforcement rapid-setting mineral-based cementitious material according to claim 1 is characterized in that The calcium oxide content in the quicklime is more than 80%.
4. The high-efficiency water-blocking and fast-setting mineral-based cementitious material for tunnel lining according to claim 1 is characterized in that The average thickness of the graphene oxide nanosheets is 1 nm.
5. The tunnel lining high-efficiency water blocking and reinforcement rapid-setting mineral-based cementitious material according to claim 1 is characterized in that The water reducer is a polycarboxylic acid high performance water reducer or a naphthalene high efficiency water reducer.
6. The tunnel lining high-efficiency water blocking and reinforcement rapid-setting mineral-based cementitious material according to claim 5 is characterized in that The Na2SO4 content in the naphthalene-based high-efficiency water reducer is less than 3%, and the water reduction rate of the polycarboxylic acid high-performance water reducer is 15-25%.
7. The high-efficiency water-blocking and fast-setting mineral-based cementitious material for tunnel lining according to claim 1 is characterized in that The fly ash is secondary fly ash or primary fly ash.
8. The tunnel lining high-efficiency water blocking and reinforcement rapid-setting mineral-based cementitious material according to claim 1 is characterized in that The retarder is citric acid.
9. A method for using the tunnel lining high-efficiency water blocking and reinforcement rapid-setting mineral-based cementitious material according to any one of claims 1 to 8, characterized in that The method comprises the following steps: Step 1: Evenly mix sulphoaluminate cement, silicate cement, fly ash, wollastonite powder, quicklime, retarder, alumina, potassium hydroxide, magnesium oxide, calcium sulfate, graphene oxide nanosheets and water reducer according to the above weight parts; Step 2: Add pure water and stir evenly until the viscosity of the funnel is within 30s, then it is ready to be formed.
Citation Information
Patent Citations
Cement-based rapid waterproof plugging material and preparation thereof
CN109160792A
Silane-modified graphene oxide-fly ash-based grouting material for blocking water-rich fracture zone of tunnel and preparation method of silane-modified graphene oxide-fly ash-based grouting material
CN116199458A
Mineral-based cementing material and application thereof on channel slope protection
CN116477916A
Cited By
High-pressure and high-temperature tunnel flowing water plugging material and preparation method thereof
CN121135268A